Status quo of insect pests – a decade of survey in Groundnut ecosystem: Status quo of insect pests – a decade of survey in Groundnut ecosystem - G N SHREEVANI,; SREEDEVI S CHAVAN,; B RAJANNA, (Journal of Oilseeds Research, 2023)
Groundnut, Arachis hypogea L. is an important oilseed crop and the insecticides to manage these pests increase the plant protection cost much if not taken at right time and also result in ecological imbalance. In order to minimize the cost of management and economic sustainability, real time management of the pests is the need of the hour. In this regard, monitoring of incidence of insect pests in groundnut ecosystem was carried out at Main Agricultural Research Station, University of Agricultural Sciences, Raichur, Karnataka for a period for over a decade (2012-2022). The pooled data showed that the maximum damage by Spodoptera litura Fab, and leaf miner was noticed during 45-75 days of crop growth wherein, spodoptera damage ranged from 10-25 percent while, the leafminer damage ranged from 5-20 percent. However, there was negligible damage by Helicoverpa armigera Hubner. Meanwhile, The leafhopper activity started from 35th standard week and the peak activity was noticed at the 43rd standard week with a foliage damage of 10-15 per cent which continued up to 45th standard week. Later on, the per cent foliage damage due to leafhopper gradually declined. Similarly, the peak activity of thrips was noticed during 40th standard week (4.0/ terminal bud) which continued till 43th standard week and thereafter the population declined.